The Building a Halal Product Assurance System: The Decision-Making Role of the MUI Fatwa Committee - Anwar, Yuqdha Aulia; Andaryuni, Lilik (International Journal on Advanced Science, Education, and Religion, 2025)
Indonesia is a country with a Muslim-majority population, reaching approximately 86.88% of the total population or around 236.59 million people. This fact makes the demand for halal food and beverage products highly essential. The halal status of a product is not only seen as a fulfillment of religious obligations but also as a consumer right to access safe, proper, and faith-compliant products. In this context, the halal label serves as a crucial indicator for Muslim consumers in selecting products for consumption. It is also perceived as a form of transparency from producers and an effective marketing strategy to attract Muslim consumer segments. However, public understanding of the halal label remains limited and is often perceived merely as a symbol, rather than as part of a comprehensive product assurance system. This study aims to examine the extent to which Muslim consumers in Indonesia consider halal aspects when choosing food and beverage products. Furthermore, it seeks to identify public perceptions regarding the importance of halal labeling and to what extent it influences purchasing decisions. The method used in this study is a literature review, by analyzing various literature sources and previous research related to Muslim consumer behavior towards halal labels. The results of this research are expected to provide a comprehensive overview of the role of halal labeling in the consumer decision-making process in Indonesia